HIV-related stigma in the UK then and now: to what extent are we on track to eliminate stigma? A qualitative investigation - Barbara Hedge; Karrish Devan; Jose Catalan; Anna Cheshire; Damien Ridge (BMC Public Health, 2021)
Abstract Background The introduction of effective antiretroviral treatment in the late 1990s led to the perception that HIV was a chronic but manageable condition. Nevertheless, stigma remains one of the major hurdles for people living with HIV (PLWH) to accessing healthcare and biomedical preventions. Thus, Fast Track Cities has set a target of zero HIV discrimination by 2030 as part of its strategy to end HIV transmission. Methods Fifty-three participants from the United Kingdom, including PLWH (n = 21, 40%), health and social care workers (n = 24, 45%), and charity workers and activists (n = 13, 25%), were recruited. Semi-structured interviews investigated stigma and discrimination, focusing on both before and after the widespread use of effective antiretroviral treatment in the late 1990s. Data were analysed using a thematic approach. Results Before effective antiretroviral treatment narratives were shaped by two main themes: 1) the media’s role in influencing public opinion and contributing to misunderstandings of HIV transmission; and 2) personal experiences of HIV-related stigma, which for PLWH included incidents of physical violence and aggression, as well as fears of their HIV status being publicised. Contemporary narratives on stigma experiences were organised around four themes: 1) discrimination in healthcare settings; 2) stigma amongst men who have sex with men (MSM); 3) stigma towards African and Afro-Caribbean PLWH; and 4) the limits of change in public HIV-related knowledge and attitudes. Contemporary narratives indicated a reduction in enacted stigma, but continued anticipation of discrimination and self-reported shame, particularly in MSM and African and Afro-Caribbean PLWH. Conclusion The nature of stigma against those with HIV has evolved. The intersection of PLWH and minority groups (e.g. MSM and African and Afro-Caribbean persons) may enhance anticipatory and internalised stigma, with some suggestion that this may contribute to reduced engagement in HIV care and prevention services. Our findings indicate the need for further research in this area, as well as proactive interventions with community groups to enhance knowledge of HIV.